In situ analysis of acupuncture protecting dopaminergic neurons from lipid peroxidative damage in mice of Parkinson's disease. Issue 4 (11th March 2022) - Zuo, Tingting; Xie, Mo; Yan, Meiling; Zhang, Zengyan; Tian, Tian; Zhu, Ying; Wang, Lihua; Sun, Yanhong
Abstract: Objectives: Acupuncture stimulation has proven to protect dopaminergic neurons from oxidative damage in animal models of Parkinson's disease (PD), but it remains unclear about the in situ information of biochemical components in dopaminergic neurons. Here, we aimed to analyse in situ changes of biochemical components and lipid peroxidation levels in dopaminergic neurons in PD mice treated with acupuncture by synchrotron FTIR micro‐spectroscopy technique. Materials and Methods: About 9–10‐week‐old C57BL/6 mice were used to establish PD model by intraperitoneal injection of 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP, 30 mg/kg for 5 days). Acupuncture stimulation was performed once a day for 12 days. Behaviour test was determined using the rotarod instrument. Biochemical compositions of dopaminergic neurons in substantia nigra pars compacta were analysed by synchrotron FTIR micro‐spectroscopy technique. The number and ultrastructure of dopaminergic neurons were respectively observed by immunofluorescence and transmission electron microscopy (TEM). Results: We found that the number and protein expression of dopaminergic neurons in MPTP‐treated mice were reduced by about half, while that in the mice treated by acupuncture were significantly restored. Acupuncture treatment also restored the motor ability of PD mice. The results of single cell imaging with synchrotron FTIR micro‐spectroscopy technique showed that the proportion of lipid in MPTP treated mice increased significantly. Especially the ratio of CH2 asymmetric stretching and CH3 asymmetric stretching increased significantly, suggesting that MPTP induced lipid peroxidation damage of dopaminergic neurons. It is also supported by the result of TEM, such as mitochondrial swelling or atrophy, loss of mitochondrial crests and mitochondrial vacuolization. Compared with MPTP treated mice, the proportion of lipid in acupuncture treated mice decreased and the mitochondrial structure was restored. Conclusions: Acupuncture can inhibit the level of lipid peroxides in dopaminergic neurons and protect neurons from oxidative damage. The study provides a promising method for in situ analysis of biochemical compositions in PD mice and reveals the mechanism of acupuncture in treating neurodegenerative diseases. Abstract : Synchrotron FTIR micro‐spectroscopy technique was used to analyse in situ changes of biochemical components and lipid peroxidation levels in dopaminergic neurons in Parkinson's disease (PD) mice treated with acupuncture. Results showed that the lipid proportion increased significantly in MPTP induced PD mice, including the ratio of lipid to protein, the ratio of lipid to nucleic acid and the ratio of CH2 asym str to CH3 asym str. In particular, the increase of the ratio of CH2 asym str to CH3 asym str implies the higher level of lipid peroxidation. The acupuncture stimulation at Yanglingquan (GB34) acupoints lowered the lipid proportion in dopaminergic neurons of PD mice brain. Our study successfully assesses acupuncture inhibiting oxidative stress damage in dopaminergic cells by in situ analysis of FTIR micro‐spectroscopy.